Bahamas. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in the Bahamas during 2011 are identified, with respect to the needs and interests of the country, strengthening issues such as animal nutrition, fodder, post-harvest, agribusiness, safety, trade, production, agricultural development and value chains. of ruminants, sheep, goats, cattle, fruits, vegetables, and coconut.